Transport properties of H2 confined in carbide-derived carbons with different pore shapes and sizes. (December 2019) - Härmas, Riinu; Palm, Rasmus; Russina, Margarita; Kurig, Heisi; Grzimek, Veronika; Härk, Eneli; Koppel, Miriam; Tallo, Indrek; Paalo, Maarja; Oll, Ove; Embs, Jan; Lust, Enn
Abstract: Hydrogen adsorption in highly porous carbon with well-defined pores, with three different shapes, and different sizes ranging from sub-to nanometers is investigated. Using a combined approach of volumetric gas adsorption method and in-situ quasi-elastic neutron scattering method the relationship between final macroscopic intake properties, details of the local adsorbent structure and the molecular behaviour of confined hydrogen are established. It is shown that sub-nanometer pores of spherical and cylindrical shape strongly limit the diffusion of H2, and thus, enhance the H2 storage capability of carbons with well-tailored pore structure. In mesoporous carbide-derived carbon, the formation of a hydrogen layer with reduced mobility close to the pore walls is observed. With the increase in the amount of confined hydrogen and the occupation of the centre pore area, the mobility of confined hydrogen increases in a jump–like fashion. Surprisingly, the increase of hydrogen diffusion is also observed at higher hydrogen loadings, indicating that cooperative H2 –H2 interactions might play a role. Graphical abstract: Image 1009